2017
DOI: 10.1111/1750-3841.13671
|View full text |Cite
|
Sign up to set email alerts
|

E‐Beam Irradiation for Improving the Microbiological Quality of Smoked Duck Meat with Minimum Effects on Physicochemical Properties During Storage

Abstract: This study was performed to evaluate the effect of different doses (0, 1.5, 3, and 4.5 kGy) of e-beam irradiation on the quality parameters (pH, Hunter's parameter, and heme pigment) and stability qualifiers (peroxide value [POV], thiobarbituric acid reactive substances [TBARSs], and total volatile basic nitrogen [TVBN]) of smoked duck meat during 40 d of storage under vacuum packaging at 4 °C. The initial populations of total bacteria (7.81 log CFU/g) and coliforms (5.68 log CFU/g) were reduced by approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
11
12
0
Order By: Relevance
“…The results depicted that the treated chicken meat had higher values of TAB and coliforms in aerobic packaging as compared to vacuum packaging, while lower counts were found in the treated samples, which are in agreement with the findings of Montiel et al; [29] they reported that irradiation of 1 and 2 kGy doses significantly curtailed the total viable counts in smoked salmon by 2 and 2.4 log units, respectively. [30] reported that irradiation reduced the load of bacteria and improved the shelf life, which is in agreement with the results of our study. The results of our study are also in agreement with the outcomes of, [31] who reported that irradiation at 5°C reduced the natural flora on chicken skin from 10 4 -10 5 to 10-500 cells/7 cm 2.…”
Section: Microbial Qualitysupporting
confidence: 93%
See 1 more Smart Citation
“…The results depicted that the treated chicken meat had higher values of TAB and coliforms in aerobic packaging as compared to vacuum packaging, while lower counts were found in the treated samples, which are in agreement with the findings of Montiel et al; [29] they reported that irradiation of 1 and 2 kGy doses significantly curtailed the total viable counts in smoked salmon by 2 and 2.4 log units, respectively. [30] reported that irradiation reduced the load of bacteria and improved the shelf life, which is in agreement with the results of our study. The results of our study are also in agreement with the outcomes of, [31] who reported that irradiation at 5°C reduced the natural flora on chicken skin from 10 4 -10 5 to 10-500 cells/7 cm 2.…”
Section: Microbial Qualitysupporting
confidence: 93%
“…The results showed that the treated samples of chicken meat have a lower content of Mb in aerobic packaging, but in the cases of MbO 2 and MMb, lower contents were found in vacuum packaging; however, a higher content of Mb was found in the untreated sample (control), and in MbO 2 and MMb, higher contents were found in treated samples, which is agreement with the findings of, [30] who reported that a higher level of Mb was found in the control samples on 0 day under aerobic packaging, but at 4.5 kGy the lowest level was found. In the samples that were irradiated with 4.5 kGy, higher levels of MbO 2 and MMb were found on the 40th day of storage under aerobic packaging, while in the non-irradiated control sample (0 kGy), low levels of MbO 2 and MMb were found on 0 day.…”
Section: Haem Pigmentsupporting
confidence: 89%
“…The results are in agreement with the findings of Kim et al (2013) who reported that application of e-beam dose to pork jerky led to the reduction in TAB count from 4.54 to 2.81 Log CFU/g. Recently, the results were further supported by the reports of An et al (2017) who depicted that there was reduction in TAB and coliforms were obtained in duck meat.…”
Section: Resultssupporting
confidence: 60%
“…These results are also concordant to the estimations of Arshad et al (2019), who reported that metmyoglobin contents significantly increased with the increase in the irradiation dose of 3 kGy in chicken meat. Furthermore, the results are supported by the outlines of An, Arshad, Jo, Chung, and Kwon (2017) who depicted that oxymyoglobin and metmyoglobin of the irradiated duck meat which was being smoked, increased significantly with the increase in the dose of irradiation (1.5-4.5 kGy).…”
Section: Heme Pigment and Hunter Color Changes In Fdmsupporting
confidence: 58%